2016
DOI: 10.1136/bmjopen-2016-011401
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a pharmacist-led educational intervention to reduce the use of high-risk abbreviations in an acute care setting in Saudi Arabia: a quasi-experimental study

Abstract: ObjectivesTo evaluate the effectiveness of a pharmacist-led educational intervention to reduce the use of high-risk abbreviations (HRAs) by healthcare professionals.DesignQuasi-experimental study consisting of a single group before-and-after study design.SettingA public emergency hospital in Mecca, Saudi Arabia.Participants660 (preintervention) and then 498 (postintervention) handwritten physician orders, medication administration records (MRAs) and pharmacy dispensing sheets of 482 and 388 patients, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 20 publications
0
20
0
4
Order By: Relevance
“…Haseeb et alconsidered the pharmacist intervention through a series of interactive lectures delivered by an experienced clinical pharmacist to all hospital staff members and dissemination of educational tools (flash cards, printed list of high-risk abbreviations (HRAs), awareness posters) designed in line with the recommendations of the Institute for Safe Medical Practices and the US Food and Drug Administration. 46 From these studies, we can conclude that the pooled analysis supported the role of pharmacists in reducing preventable ADEs and prescribing errors. Because, these studies show different methods of interventions by the clinical pharmacists to decrease the prescribing errors, in addition to the promising effects of the expansion of the role of the pharmacist in the prescribing process and the pharmacist's interventions due to CPOE for decreasing the prescription errors.…”
Section: Iii-pharmacist Interventionmentioning
confidence: 58%
See 1 more Smart Citation
“…Haseeb et alconsidered the pharmacist intervention through a series of interactive lectures delivered by an experienced clinical pharmacist to all hospital staff members and dissemination of educational tools (flash cards, printed list of high-risk abbreviations (HRAs), awareness posters) designed in line with the recommendations of the Institute for Safe Medical Practices and the US Food and Drug Administration. 46 From these studies, we can conclude that the pooled analysis supported the role of pharmacists in reducing preventable ADEs and prescribing errors. Because, these studies show different methods of interventions by the clinical pharmacists to decrease the prescribing errors, in addition to the promising effects of the expansion of the role of the pharmacist in the prescribing process and the pharmacist's interventions due to CPOE for decreasing the prescription errors.…”
Section: Iii-pharmacist Interventionmentioning
confidence: 58%
“…Most studies suggested that engaging pharmacists in these ways can be beneficial, but few studies have explored the best ways to integrate pharmacists into teams and the interprofessional factors to be considered. [39][40][41][42][43][44][45][46] The intervention of the pharmacist differs between the studies, for example,Kaushal et al addressed full-time pharmacists participation in physician rounds and provided physicians with timely information and advice on ADEs; drug interactions; and appropriate dosages, dose intervals, and routes of administration. 39 Klopotowska et alreviewed the interventional role of two hospital pharmacistswith 10 years of experience who completed 4 weeks of training in the ICU before the start of this study to guarantee the quality of intervention.…”
Section: Iii-pharmacist Interventionmentioning
confidence: 99%
“…Los de alto riesgo se refirieron a las abreviaturas contenidas en la lista que emitió el ISMP 9 . Según un estudio realizado en Arabia Saudita el año 2016, la incidencia del uso de abreviaturas de alto riesgo en la prescripción médica correspondió a 72,7% 20 , se trató de abreviaturas que pudieron causar consecuencias mortales en los pacientes, tales como "u o iu", las que pudieron ser erróneamente confundidas por un 0 o por un 4, con riesgo de multiplicar por 10 o más la dosis (por ejemplo, 4U pudo haberse confundido con 40) 21 . Autores señalaron, que independiente si las abreviaturas eran de alto o bajo riesgo, éstas debían ser evitadas 4 .…”
Section: Abreviaturas Comúnmente Utilizadas En Las Prescripciones Médunclassified
“…Sumado a lo previo, existió consenso entre los profesionales prescriptores, de que la utilización de abreviaturas en su trabajo diario economizaba su tiempo, no obstante, estaban en conocimiento de que éstas podían ser mal interpretadas o podían tener más de un significado para los lectores. Además de ello, los profesionales médicos asumieron desconocer las abreviaturas que podían causar un gran daño al paciente 11,15,20,24 .…”
Section: Causas Del Uso De Abreviaturas En Saludunclassified
See 1 more Smart Citation